1979
DOI: 10.1126/science.451551
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Promotes Lymphoma Incidence in Rats

Abstract: Rats were exposed to sodium nitrite in food or water at concentrations of 0, 250, 1000, and 2000 parts per million. Lymphoma was increased in all groups fed nitrite; the overall combined incidence was 5.4 percent in 573 control rats and 10.2 percent in 1383 treated rats. The mechanism of cancer induction did not appear to be through the formation of nitrosamines but through a more direct effect of nitrite on the lymphocyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…N-nitrosoamines, which react with nucleic acids, are highly carcinogenic in laboratory animals (Gangolli et al, 1994) and could also be associated with human cancer (Bartsch and Montesano, 1984;Craddock, 1983). A report published in 1979 that dietary nitrite caused lymphomas in rats (Newberne, 1979) (Speijers and Brandt, 2003). Indeed, a diet rich fruit and vegetables, which far exceeds the WHO acceptable daily intake of nitrate, is not associated with an increase in deaths from cancer (Hung et al, 2004).…”
Section: Potential For Detrimental Effects Of High Nitrate Intakementioning
confidence: 97%
“…N-nitrosoamines, which react with nucleic acids, are highly carcinogenic in laboratory animals (Gangolli et al, 1994) and could also be associated with human cancer (Bartsch and Montesano, 1984;Craddock, 1983). A report published in 1979 that dietary nitrite caused lymphomas in rats (Newberne, 1979) (Speijers and Brandt, 2003). Indeed, a diet rich fruit and vegetables, which far exceeds the WHO acceptable daily intake of nitrate, is not associated with an increase in deaths from cancer (Hung et al, 2004).…”
Section: Potential For Detrimental Effects Of High Nitrate Intakementioning
confidence: 97%
“…In the late 1970s, researchers found that ingestion of nitrite could cause tumours in rats 20. After some initial debate regarding the mechanism,21 a theory to explain the carcinogenic effects of nitrite emerged.…”
Section: Nitrosamines and Cancermentioning
confidence: 99%
“…A Food and Drug Administration (FDA)-supported study reported that nitrite doubles the risk of lymphomas in rat 62 and suggested that it increased cancer incidence and tumor growth rate in animal studies 91 . Nevertheless, the human studies did not clarify this issue.…”
Section: Nitrite On Demand Local But Systemically Administered No Dmentioning
confidence: 99%